Network disruption detected in MZ (Mozambique) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Mozambique. Data sourced from IODA.
Network Disruption Incident ID: MZ-2026-0001. Severity: critical. Confidence: 70%